SAT0532 Treatment with methotrexate and risk of ischaemic relapses in patients with giant cell arteritis in clinical practice. (12th June 2018) - Font Urgelles, J.; Rosales Rosado, Z.; Freites Núñez, D.D.; Lois bermejo, P.M.; Mateos, León; Morado Quiñoa, I.C.; Pato Cour, E.; Jover Jover, J.A.; Alcázar, L. Abásolo
Abstract : Background: Clinical trials show the efficacy of Methotrexate (MTX) in giant cell arteritis (GCA). It is necessary to corroborate these results in real life. Objectives: To assess the incidence and the risk of ischaemic relapses in GCA patients treated with and without Methotrexate (MTX) in clinical practice. Methods: Retrospective longitudinal observational study. Subjects: patients treated at the Rheumatology Service of the Hospital Clínico San Carlos with the diagnosis of GCA. They were included from the date of diagnosis (January 1991 to September 2013) and followed-up until lost of follow up or Sept-2014. Main outcome : relapses by isquemic event (RIE): Presence of mandibular claudication, visual manifestations (blurred vision, diplopia, transient or permanent loss of vision), cerebrovascular accident, ischaemic heart disease or claudication of limbs, after having achieved an objective improvement, associated with an increase in the erythrocyte sedimentation rate (ESR) and the need to increase corticosteroids (at least 10 mg over the previous dose). Independent variable: exposure to MTX over time. Secondary variables : sociodemographic, clinical and treatment. Statistical analysis : RIE rates were assessed by survival techniques, expressing the incidence per 100 patients*year with their 95% confidence interval [CI]. The influence of MTX on the REI was analysed by multivariate Cox regression models. Results were expressed as Hazard ratios (HR) with their respective CI. Results: 168 patients were included with a follow-up of 675.59 patients*year. 80.36% were women (mean age: 76.77±7 years). The most prevalent comorbidities were arterial hypertension (64%), dyslipidemia (34%), cardiovascular pathology (30%) and polymyalgia rheumatica (13.77%). The most common clinical symptom at diagnosis was headache (87.43%), systemic involvement (55%) and polymyalgia rheumatica (49.70%). The ESR was 78±30.85 mmHg and Hb of 12.06±1.58 mg/dL. 46.39% had a positive biopsy. 64% were on MTX (mean dose: 10 mg) at any time during the follow-up, from those 68% started MTX in the first 4 weeks after diagnosis. The mean dose of corticosteroids was 50.72±15.46 mg. There were 21 relapses by ischaemic events (12.5%), with an incidence of 3.1 [2.02–4.77]. The median time to first RIE was 0.4 [p25–75: 0.4–5.1] years. The incidence of RIE in patients exposed to MTX was 1.92 [0.8–4.62], whereas in those without MTX was 3.84 [2.36–6.28]. The incidence of REI in women was 3.44 [2.17–5.46] and in men was 1.97 [0.6–6]. In the multivariate analysis after adjusting for age, sex, disease activity and calendar time, exposure to MTX had less risk of relapse by ischaemic event compared to those without MTX (HR 0.3 [0.096–0.99]; p=0.048). Conclusions: The frequency of REI was 12.5%. The incidence of REI was 3% patients-year. With the results observed in this study, the use of MTX seems to decrease the risk of relapses by ischaemic event. Disclosure of Interest: None declared